POTENSI TAMAN MANGROVE PULAU PRAMUKA SEBAGAI DESTINASI EDUTOURISM - Muzani Muzani; A. Purwindiyanto A. Purwindiyanto; E.S. Meylani E.S. Meylani; R. Andika R. Andika; R. Nurfadilah R. Nurfadilah (Lambung Mangkurat University-Indonesia, 2020)
Mangrove Park of Pramuka Island is an A-list tourism object in Thousand IslandsRegency, Jakarta Special Region Province. Mangrove holds economical and ecological advantage, such as absorbing and storing blue carbon. The storing ability is more durable and one hundred times bigger than land forest. By edutourism, high school students are able to learn in an enjoyable environment about coastal ecosystem and its interaction with human. Qualitative analytical method is used to generate compatibility value and SWOT analytics in order to discuss the potential of Mangrove Park of Pramuka Island as edutourism object for high school student to increase comprehension of blue carbon concept. Promotion and availability of educative supporting aspect may boost more edutourist from high schools all over Jakarta Special Region Province.